Utilization of AI Technology in Translation Among Arabic Language Students at PTKIN in North Sumatra - Darman, Isra Hayati; Hakim, Rani Ismil; Refdianti, Afrina (Aphorisme: Journal of Arabic Language, Literature, and Education, 2025)
This study describes the use of Artificial Intelligence (AI) among Arabic language students at several Islamic State Higher Education Institutions (PTKIN) in North Sumatra. Although the use of AI as a tool to assist in translating Arabic texts offers significant benefits for students, its negative impacts cannot be entirely avoided. The study aims to examine in depth how Arabic language students at these PTKIN utilize AI applications in the Arabic translation process, the reasons behind their choice of applications, as well as the positive and negative impacts on their motivation and learning outcomes. This research employs a qualitative methodology with a phenomenological approach. Data were collected through in-depth interviews, direct observation, and documentation. The research population consists of 331 Arabic language students distributed across four study programs at three PTKIN in North Sumatra. A purposive sampling technique was used to select 24 students as the research sample from these programs. The collected data were analyzed using descriptive analysis techniques. The findings indicate that the majority of Arabic language students are now actively using translation applications to support their coursework and thesis writing. The most frequently used translation applications include Google Translate, DeepL, and ChatGPT. The use of AI greatly assists students in simplifying the translation of their assignments and improving their learning outcomes. However, on the negative side, the translation skills of many students have not improved, as reliance on AI has led to laziness, dependency, and a lack of critical thinking.